Pelatihan, motivasi berprestasi, penguasaan kompetensi dan pengaruhnya terhadap profesionalisme guru SMP di Kota Magelang - Gunanto, Bambang Tri (Piramida Akademi, 2024)
The purpose of this study was to determine how much contribution effect training of participation, achievement motivation, and mastery of pedagogical competence simultaneously and partially to the teachers professionalism of Junior High School in Magelang City 2017/2018 academic year. This research is a quantitative type of research. The population in this study were all Public Junior School teachers in Magelang City, which numbered 496 people for level of error of 5% or 95% confidence level. The number of this sample was 178 people. The sampling technique uses proportional random sampling. Data collection is done through questionnaires. Data analysis techniques using multiple regression analysis, analysis techniques prerequisite analysis include normality test, linearity test, and multicollinearity test, regression analysis, F test, partial correlation and determination test. After validity and reliability tests were obtained that 29 questions from 30 items of questions motivation for valid and reliable achievement, 30 questions of pedagogic competence and 30 questions of teacher professionalism all declared valid and reliable. The results of this study indicate that the Education Quality Management there is positive and significant participation of the training, achievement motivation, mastery of pedagogical competence of the teachers' professionalism Junior High School in Magelang year 2017/2018, meaning that the higher participation of the training, achievement motivation and competence of a pedagogic then Professionalism teachers will increase. The results of the research can be used as input for principals and teachers to improve the professionalism of teachers.